Overexpression of cyclin D1 induces the reprogramming of differentiated epidermal cells into stem cell-like cells. Issue 5 (3rd March 2016) - Zhao, Along; Yang, Leilei; Ma, Kui; Sun, Mengli; Li, Lei; Huang, Jin; Li, Yang; Zhang, Cuiping; Li, Haihong; Fu, Xiaobing
ABSTRACT: It has been reported that Wnt/β-catenin is critical for dedifferentiation of differentiated epidermal cells. Cyclin D1 (CCND1) is a β-catenin target gene. In this study, we provide evidence that overexpression of CCND1 induces reprogramming of epidermal cells into stem cell-like cells. After introducing CCND1 gene into differentiated epidermal cells, we found that the large flat-shaped cells with a small nuclear-cytoplasmic ratio changed into small round-shaped cells with a large nuclear-cytoplasmic ratio. The expressions of CK10, β1-integrin, Oct4 and Nanog in CCND1 induced cells were remarkably higher than those in the control group ( P < 0.01). In addition, the induced cells exhibited a high colony-forming ability and a long-term proliferative potential. When the induced cells were implanted into a wound of laboratory animal model, the wound healing was accelerated. These results suggested that overexpression of CCND1 induced the reprogramming of differentiated epidermal cells into stem cell-like cells. This study may also offer a new approach to yield epidermal stem cells for wound repair and regeneration.